Deep cervical stromal invasion predicts poor prognosis in patients with stage II endometrioid endometrial cancer: a two-centered retrospective study - Shao, Wenyu; Xue, Yu; Xu, Zhiying; Guan, Jun; Wang, Huaying; Chen, Xiaojun; Ren, Yulan (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the impact of depth of cervical stromal invasion (CSI) on the prognosis of International Federation of Gynecology and Obstetrics (FIGO) stage II endometrioid endometrial cancer (EEC).MethodsPatients with FIGO stage II EEC confirmed by postoperative histopathology and consecutively admitted to the Obstetrics and Gynecology Hospital of Fudan University and Fudan University Shanghai Cancer Center between 2008 and 2017 were included in this study and reviewed retrospectively.ResultsTwo hundred and ninety-seven patients were included in this study. There were 253 (253/297, 85.2%)patients with superficial (<50%) and 44 (44/297, 14.8%) cases with deep (≥50%) CSI. The median follow-up time was 75.0 months (range: 5-175 months). Patients in the ≥50% CSI group had a poorer prognosis compared to the <50% CSI group (recurrence-free survival [RFS]: adjusted hazard ratio [aHR] = 6.077, 95% Confidence Interval [CI]: 2.275-16.236, disease-specific survival [DSS]: aHR = 7.259, 95% CI: 2.546-20.695). Deep CSI was an independent predictor of local recurrence (aHR=5.537, 95% CI: 1.804-16.991). Post operative external beam radiation therapy (EBRT) was correlated with a reduced risk of recurrence (aHR = 0.288, 95% CI: 0.097-0.859).ConclusionDeep CSI is a poor prognostic factor for RFS and DSS in patients with FIGO stage II EEC. Postoperative EBRT can improve both RFS and DSS. Those findings imply that a detailed pathological report on the depth of CSI would be helpful in better understanding its impact on prognosis and selecting an appropriate postoperative treatment for the patient.